Two new species of Basilia Miranda-Ribeiro, 1903 (Diptera: Nycteribiidae), members of the ferruginea group, from Southern Brazil - Graciolli, Gustavo (Zootaxa, 2003)
Two new species of Basilia Miranda-Ribeiro, 1903, B. insularis sp. nov. and B. ruiae sp. nov., from Southern Brazil are described. Characters justifying the new species include, the female abdomen, male genitalia and male femur II. Relationships with similar species those of (B. ferruginea Miranda-Ribeiro, 1903 and B. handleyi Guimarães, 1966) are discussed.